Assessment of Traffic Noise Pollutions Outside School, Residential, Hospital and Commercial Areas along Jalan Kluang, Batu Pahat, Johor - Chandira Segaran, Viknheswar (International Journal of Integrated Engineering, 2019)
The increasing numbers of vehicles are the major factor that contributes to the noise pollution. Some of the residential areas and schools near busy traffic road were built many years before the development took place. Major effects of traffic noise pollution include interference with communication, sleeplessness and reduced efficiency. In Malaysia, a guideline for environmental noise limit has been set by Department of Environment (DOE) in order to minimize traffic noise pollution. The aim of this study is to assess the traffic noise pollution occurred in residential, school, hospital and commercial areas along Jalan Kluang, Batu Pahat, Johore, Malaysia. Traffic noise measurement consists of 9 survey locations were carried out using data logger Type RS-322 along with traffic volume. The assessments were carried out during peak hours which covered morning peak hours (7.00 a.m. to 9.00 a.m.) and evening peak hours (5.00 p.m. to 7.00 p.m.). Traffic noise indicators of LAeq, L10, L90, Traffic Noise Index (TNI) and Noise Pollution Level (LNP) were estimated in the present study. Besides, the recorded noise levels were also compared with the permissible limit that has been set in Malaysian legislation. The overall traffic noise assessments for all 9 locations along the Jalan Kluang were beyond the standard limit set by DOE during daytime. The noise produced by the traffic along the Jalan Kluang, Batu Pahat is considerably high and could lead to serious impact to the quality of life.